P250 The microbial landscape of the upper and lower respiratory tract in PWCF and healthy individuals. (12th November 2019) - Einarsson, GG; Lord, RW; Lee, AJ; Smith, JA; Elborn, JS; Jones, AM; Tunney, MM
Abstract : Background: Historically during microbiological observations sputum has been thought to represent the 'lower' airway or the lung environment. However, during expectoration sputum passes through the oropharynx, potentially resulting in contamination by oropharyngeal microorganisms. Methods: Matched sputum (SPU) on oropharyngeal rinse (OPR) samples were collected from people with cystic fibrosis (PWCF; n=40) and healthy volunteers (HV; n=6). Genomic DNA was extracted and microbial community profiles determined by sequencing the V4 region of the 16S rRNA marker gene using the Illumina MiSeq platform. Changes in microbial community composition, alpha- (richness, Shannon-Wiener diversity, evenness, dominance) and beta-diversity (ADONIS [PERMANOVA] and mean distance to group centroid) were compared between sampling sites (SPU vs. OPR) within groups (PWCF and HV), and between cohorts (PWCF vs. HV). Results: At the level of phyla, CF-SPU showed significant enrichment in the mean relative abundance for Proteobacteria when compared to CF-OPR, HV-OPR and HV-SPU samples (p=4.10*10– 15 ). Conversely, CF-OPR, HV-OPR and HV-SPU samples contained significantly higher levels of Firmicutes compared to CF-SPU samples (p=8.24*10– 11 ). For the main genera, CF-SPU demonstrated higher relative abundance of Pseudomonas spp. (p=1.80*10– 6 ; FDR-adjusted) when compared to CF-OPR, HV-OPR and HV-SPU. Similarly, for Streptococcus spp. the observed relative abundance was higher in CF-OPR, HV-OPR and HV-SPU samples when compared to CF-SPU (p=5.50*10– 5 ; FDR-adjusted). Comparison between PWCF and HV showed significantly lower alpha-diversity in PWCF when compared to HV, with CF-SPU showing significantly lower richness, Shannon-Wiener diversity and evenness (p=8.76*10– 11, p=3.21*10– 10 and p=0.02, respectively) and higher dominance (p=1.54*10– 8 ) when compared to CF-OPR, HV-OPR and HV-SPU, respectively. For beta-diversity, permutation-based statistical testing showed a significant difference between CF-SPU and CF-OPR (ADONIS; Bray-Curtis; R 2 =0.241; p=0.001; 999 permutations). In addition, comparison between PWCF and HV showed a significant difference in community structure between the two groups (ADONIS; Bray-Curtis; R 2 =0.321; p=0.001; 999 permutations). Conclusion: CF sputum samples differ considerably in their microbial community composition and structure when compared to oropharyngeal communities, suggesting a limited role for oropharyngeal contamination in determining their microbial community composition of CF-SPU. Furthermore, we show that oropharyngeal communities in PWCF lack most CF specific pathogens, and demonstrate a unique community signature when compared to healthy individuals.